2013
DOI: 10.4049/jimmunol.1300416
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Is an Early and Central Mediator of Bacterial and Sterile Inflammation In Vivo

Abstract: In vitro studies identified Y-box–binding protein (YB)-1 as a key regulator of inflammatory mediators. In this study, we observed increased levels of secreted YB-1 in sera from sepsis patients. This led us to investigate the in vivo role of YB-1 in murine models of acute peritonitis following LPS injection, in sterile renal inflammation following unilateral ureteral obstruction, and in experimental pyelonephritis. LPS injection enhanced de novo secretion of YB-1 into the urine and the peritoneal fluid of LPS-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 39 publications
5
56
0
Order By: Relevance
“…32,33 Flow-cytometric analyses of the primary cultures showed that PECs, podocytes, and mesangial cells expressed CD74, whereas only PECs and mesangial cells coexpressed CD44 ( Figure 3A), confirming our in vivo immunohistochemic data. None of the cell types showed detectable CXCR2 expression and only faint CXCR4 levels.…”
Section: Mif Receptor Expression In Glomerular Cells In Vitrosupporting
confidence: 79%
“…32,33 Flow-cytometric analyses of the primary cultures showed that PECs, podocytes, and mesangial cells expressed CD74, whereas only PECs and mesangial cells coexpressed CD44 ( Figure 3A), confirming our in vivo immunohistochemic data. None of the cell types showed detectable CXCR2 expression and only faint CXCR4 levels.…”
Section: Mif Receptor Expression In Glomerular Cells In Vitrosupporting
confidence: 79%
“…There is increasing evidence that YB-1 has an important regulatory role in various inflammatory diseases, such as allergic asthma (31), transplant rejection (17), atherosclerosis (18), sepsis, and sterile inflammation (16). In previous studies, our group identified YB-1 as a cell-type-specific regulator of the chemokine CCL5 (17,18), a key chemotactic factor for immune cell infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…Co-immunoprecipitation of CN Associated with YB-1-Prior to immunoprecipitation, polyclonal anti-calcineurin antibody (Cell Signaling) and nonspecific rabbit IgG (Santa Cruz Biotechnology) as negative control were covalently linked to protein A-Sepharose beads (50% suspension; Invitrogen), as described before (16). A total of 40 l of protein A-Sepharose coupled with either polyclonal CN antibody or nonspecific IgG was incubated with 200 g of total cell extracts or cytoplasmic (200 g) and nuclear (100 g) protein extracts from HEK293T cells, respectively, for 90 min at 4°C in immunoprecipitation buffer (20 mM HEPES, 100 mM potassium chloride, 5 mM magnesium acetate, 1 mM DTT, 0.025% Triton X-100, and protease inhibitors).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] YB-1 is a highly conserved protein involved in the regulation of inflammatory processes, including sterile inflammation in renal diseases. 19 YB-1 conveys multiple functions through its interaction with DNA, mRNA, and proteins.…”
mentioning
confidence: 99%